Mobile charging services for electric vehicles - Chin, Violet Xin Yao (Nanyang Technological University, 2024)
The rapid growth of the Electric Vehicle (EV) market has highlighted the critical need for efficient and accessible charging solutions. This study investigates consumer preferences for mobile charging services as a complement to Fixed Charging Stations (FCS), with a focus on the factors influencing their decision-making process. Through a quantitative approach, a survey was conducted among a diverse group of participants in Singapore, comprising both drivers and non-drivers. The survey aims to assess the willingness to use mobile charging services under various price points, the importance of different factors such as convenience, cost, and charging speed, and the impact of potential incentives on consumer choices. The findings revealed that convenience is the most significant factor influencing the choice of method of charging, followed by cost, charging speed, and waiting time. The study also indicates a strong preference for mobile charging services, especially when reduced waiting times and competitive pricing are offered. Financial incentives, such as discount vouchers, loyalty programs, and special pricing for memberships, were identified as effective strategies to encourage the adoption of mobile charging services. The results suggest that the integration of mobile charging services alongside FCS can significantly enhance the convenience of charging EVs and potentially increase the adoption rate of EVs. This study provides valuable insights for suppliers of mobile charging services, policymakers, and stakeholders in the EV industry, highlighting the importance of understanding consumer behaviour and preferences to promote the widespread use of EVs and support the transition towards a more sustainable transportation system.